Fetal alcohol spectrum disorders (FASD) and youth firesetting: A call on criminal justice, emergency responder, and fire prevention specialists to become informed. (27th December 2021) - Brown, Jerrod; Spiller, Vanessa; Carter, Megan; Osmonson, Kathi; Porth, Don; Bishop‐Deaton, Deanna; Jozan, Amy
Abstract: Central nervous system damage resulting from prenatal exposure to alcohol, often referred to as fetal alcohol spectrum disorders (FASD), commonly manifests as lacking cognitive functioning, problem solving, impulsivity, memory, executive functioning, and social skill deficits. For individuals with FASD, these brain‐based deficits translate into impulsive behaviors and poorly thought‐out decision‐making, coupled with an inability to anticipate and recognize the sometimes very severe consequences of their behaviors. Not unexpectedly, individuals with FASD frequently find themselves disproportionately involved in the criminal justice system and mental health services. For some individuals with FASD, these behaviors can also include firesetting. First responders, like other health and legal professionals, are often unable to recognize the behavioral indicators of FASD, primarily due to a lack of training. As a result, firesetting behaviors are often attributed to deliberate, willful acts of delinquency, a desire to damage property, thrill seeking, or as attempts for personal gain, rather than being viewed as maladaptive attempts to solve problems by individuals who lack the tools to do this in more appropriate ways. These same skill deficits also present when individuals with FASD are interviewed about their involvement in such behaviors, sometimes resulting in confabulation, suggestibility, and false confessions. Further education and training in FASD are vital for first responders if they are to better support individuals with FASD and minimize their chances of becoming involved in firesetting behaviors. Furthermore, this training and education will help ensure that first responders can intervene in more appropriately when crisis situations do occur. This article will outline key behavioral symptoms of FASD as well as provide first responders with suggestions as to how to best support individuals when FASD is suspected. The brief quote that follows highlights some of the key challenges facing individuals with FASD and how poor decision‐making and impulsiveness can result in severe consequences for the individual and those around them.